RURAL BIO ENERGY: UPAYA PEMENUHAN ENERGI ALTERNATIF SECARA MANDIRI UNTUK MENINGKATKAN KESEJAHTERAAN MASYARAKAT DESA JATI SARI - Tiara Nirmala; Sri Waluyo; Moneyzar Usman; Arivina Ratih (Yayasan Education and Social Center, 2023)
The general objective of carrying out community service activities in Jati Sari Village, Jati Agung District, South Lampung Regency is to apply the concept of rural bio-energy to farming communities in the region. Utilization of cow dung into biogas through a biogas digester will produce solid and liquid waste which can then be processed into compost/manure. Integration with the cultivation of vegetables and food crops is by utilizing the results of fertilizer from animal manure into the cultivation system. Availability of compost fertilizer can overcome the scarcity of availability and distribution of manufactured fertilizers that currently often occur. Moreover, at the present time, inorganic fertilizers are reduced in price by the government, so that the price of manufactured fertilizers is currently felt by farmers to be more expensive. Provision of compost for farming can help the government reduce subsidies, as well as improve the quality of agricultural products through the application of organic cultivation systems, and can improve the physical and chemical properties of paddy/field soil. Utilization of cattle waste is basically the application of the zero-waste concept in agricultural production systems. A clean environment can support an increase in the level of public health. All of these activities ultimately aim to empower the local farming community so that their economic level and welfare increase, and the establishment of an area (village/district) that applies bio-energy organic cultivation systems and towards food and energy self-sufficiency, as well as the establishment of partnerships between universities, local government, and the community so that the goals of economic development and public health with an environmental perspective can be realized